New Methodology for Evaluation and Project Management in Engineering - Vyslouzilova, Daniela; Sellner, Karel (Manufacturing Technology Journal, 2019)
The goal of the proposed methodology is to manage and evaluate investments across the portfolio of projects in the company, with extra focus on selecting engineering projects into the portfolio. In order to design an objective methodology, several analyses were conducted to verify a general validity of the methodology. The starting point is using methods which allow a high degree of flexibility in solving problems. The ANP method is suitable for the determination of priorities in network systems with different types of dependencies between the elements of the system. The DEMATEL method is used in this methodology to formulate the structure of relationships between the criteria of the system and obtain the criteria importance in the system. All calculations were carried out using the MAXIMA and Super Decisions software. The proposed methodology has been verified on a case study using real-life data supplied by the participating company. There were used methods of decision making, especially methods of operations research, linear programming and team expert selection methods.
Keywords: ANP method; DEMATEL method; Operations research; Project portfolio Management